Space-time Estimates for Parabolic Type Operator and Application to Nonlinear Parabolic Equations (Journal of Partial Differential Equations, 2020)
In this present paper we establish space-time estimates of solutions for linear parabolic type equations based on classical multipliers theory or operator semigroup theory. According to space-time estimates we first construct suitable work space L^q(0, T; L^P), moreover we study the Cauchy problem and initial boundary value problem for semilinear parabolic equation in L^q(0, T; L^P) type space.